PENILAIAN DAMPAK HUTAN KEMASYARAKATAN MELALUI SUSTAINABLE LIVELIHOODS FRAMEWORK - Helen Yuseva Ayu; Hari Kaskoyo; Slamet Budi Yuwono; Irwan Sukri Banuwa; Rahmat Safe’i (Lambung Mangkurat University-Indonesia, 2022)
Management forest area in concurrently through community forestry programs is an alternative to social forestry programs that involve communities to reduce problems with forest resource pressures. Gapoktan Beringin Jaya is one of the community forest groups bring of forest management and utilization activities by empowering local communities that have an impact on sustainable livelihoods. Therefore to find out the impact is carried out with the sustainable livelihoods framework to evaluate the impact and find out sustainable livelihood strategies. The results of this study are changes in community forestry that occur significantly through the sustainable livelihoods framework for livelihood assets, which are natural capital including owned land, timber species and non-timber forest product types. Human capital includes the type of training and the number of children going to school. Financial capital includes sources of income and loans. Social capital includes organizations, social networks, levels of trust and mutual assistance, and physical capital includes housing conditions, the number of motor vehicles and the number of electronic equipment.